2012
DOI: 10.1007/s00202-012-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on a choice of stator slot skew angle in brushless PM machines

Abstract: The paper investigates the effects of stator slot skewing in a permanent magnet brushless DC motor. A simple analytic formula for calculation of the best angle of stack skew, which leads to nearly total reduction of the cogging torque, is developed. The skew angle obtained from this formula is different to that used by the designers of PM brushless motors. The analysis is carried out for a fractional horsepower brushless permanent magnet motor with the surface-mounted magnets using a time-stepping, multi mesh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The formulation relies on 'slicing' the region, where individually the field is treated as 2D, and then 'stitching' them together with some conditions on flux continuity. The 2.5D approach is well known and often used [4,6].…”
Section: Strategies For Pmm Design Using Field Modelsmentioning
confidence: 99%
“…The formulation relies on 'slicing' the region, where individually the field is treated as 2D, and then 'stitching' them together with some conditions on flux continuity. The 2.5D approach is well known and often used [4,6].…”
Section: Strategies For Pmm Design Using Field Modelsmentioning
confidence: 99%
“…The results showed that optimizing the BLDC IPM motor to reduce cogging torque yields remarkable results, specifically when utilizing a skew angle on the stator core or, in certain cases, on the rotor core, alongside enlarging the air gap. A skew angle on the stator core can reduce almost the total of the cogging torque 10) .…”
Section: Introductionmentioning
confidence: 99%
“…One of them is to reasonably design various inherent structural parameters of the machine, such as stator slot and rotor pole combination and pole arc coefficient. Another one is to adopt various kinds of auxiliary measures, such as skewing the stator slot [1,2], skewing the rotor pole [3,4], improving the PM shape [5,6], changing the magnetization pattern of the magnet [7], and changing the geometry parameters of the stator teeth or slot [8,9]. All the above auxiliary measures can effectively make the torque ripple decrease, but these measures will largely increase manufacturing difficulty.…”
Section: Introductionmentioning
confidence: 99%